ผลของแคพไซซิน เรเซอปีน และ อัวเบนต่ออัตราการเต้นและแรงหดตัวของหัวใจห้องบนขวาและซ้ายของหนูขาวและหนูตะเภา - ประภาศรี ซังชมแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
Capsaicin 5x10 -6 M initially increased rate and force of contraction of isolated rat and guinea-pig right and left atria and followed by slight reduction below control within 15 min after drug administration. These effects don t depend on catecholamine storage in cardiac muscle. Ouabain 1x10 -6 M produce greater increased on both rate and force of contraction in guinea-pig atria than the rat atria during 15 min after administration. Alternative administration of capsaicin and ouabain within 45 sec in isolated guinea-pig showed additive effects, but not significant deference on rate and force of right atria with some cardiac arrhythmias. The depression effect of capsaicin could antagonized by ouabain. The isolated rat left atria from this experiment showed similar obtained from papillary muscle, and could suggested that has no effect on intracellular calcium released in SR. From investigation the greater response of capsaicin in guinea-pig atria than rat atria depend on substance P and CGRP. The patient intake of chili and ouabain may increase force but could produce cardiac arrhythmias.